Editor’s Highlight: Neonatal Activation of the Xenobiotic-Sensors PXR and CAR Results in Acute and Persistent Down-regulation of PPARα-Signaling in Mouse Liver - Li, Cindy Yanfei (Toxicol Sci, 2016)
Safety concerns have emerged regarding the potential long-lasting effects due to developmental exposure to xenobiotics. The pregnane X receptor (PXR) and constitutive androstane receptor (CAR) are critical xenobiotic-sensing nuclear receptors that are highly expressed in liver. The goal of this study was to test our hypothesis that neonatal exposure to PXR- or CAR-activators not only acutely but also persistently regulates the expression of drug-processing genes (DPGs). A single dose of the PXR-ligand PCN (75 mg/kg), CAR-ligand TCPOBOP (3 mg/kg), or vehicle (corn oil) was administered intraperitoneally to 3-day-old neonatal wild-type mice. Livers were collected 24 h post-dose or from adult mice at 60 days of age, and global gene expression of these mice was determined using Affymetrix Mouse Transcriptome Assay 1.0. In neonatal liver, PCN up-regulated 464 and down-regulated 449 genes, whereas TCPOBOP up-regulated 308 and down-regulated 112 genes. In adult liver, there were 15 persistently up-regulated and 22 persistently down-regulated genes following neonatal exposure to PCN, as well as 130 persistently up-regulated and 18 persistently down-regulated genes following neonatal exposure to TCPOBOP. Neonatal exposure to both PCN and TCPOBOP persistently down-regulated multiple Cyp4a members, which are prototypical-target genes of the lipid-sensor PPARα, and this correlated with decreased PPARα-binding to the Cyp4a gene loci. RT-qPCR, western blotting, and enzyme activity assays in livers of wild-type, PXR-null, and CAR-null mice confirmed that the persistent down-regulation of Cyp4a was PXR and CAR dependent. In conclusion, neonatal exposure to PXR- and CAR-activators both acutely and persistently regulates critical genes involved in xenobiotic and lipid metabolism in liver.